Diretrizes de desenvolvimento de um instrumento metaprojetual para a concepção e condução de negócios de moda - Nicoletti, Maíra Meira (Universidade do Vale do Rio dos Sinos, 2019)
Within the national economy, the fashion sector is one of the most expressive. Among the businesses belonging to the sector are the fashion brands, companies that create and sell clothing products. Many of these companies are managed by the designers themselves, who are also responsible for the collection development. However, it is observed that fashion brands do not hold for a long time in the market, being one of the main reasons linked to the management. Adding to the complexity of the sector, which encompasses different levels of activities and actors, particular ways of creating and managing companies belonging to this segment are necessary. In this context, the present study assumes that a design-oriented instrument could assist in the design of new fashion businesses. It is known that today the performance of the discipline goes beyond the sense once given, essentially related to the product development. Thus, the concept of a metadesign, associated to strategic design, is presented as a space that favors reflection and learning during the design of a business. In this way the general objective of this work is to propose guidelines for the development of a metadesign instrument for the conception of fashion business. For that, interviews were conducted with fashion entrepreneurs to better understand the process of opening their brands. From the analysis of content, the main result was the lack of reflection on the part of enterprising fashion designers to open their brands. In addition, there was a certain difficulty in adapting to the traditional methods and procedures used to create business models. This aspect has been related to the design thinking and the lack of management knowledge. In view of this, it was found that a metaprojectual tool used to conceive new business can be relevant, since it allows to research, reflect and learn within this process guided by a design culture. As a final result, the research presents seven guidelines for the development of this instrument, understanding that it is able to guide the creation of business from another perspective, more systemic, creative and particular to the field of fashion.
Keywords: Design Estratégico; Metaprojeto; Moda; Modelos de negócios; Strategic Design; Metadesign; Fashion; Business Model; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial